The Influence of Using the Google Earth Application on Cronological Thinking in Class X Indonesian History Learning at MA Al-Khairiyah Rancaranji: Pengaruh Penggunaan Aplikasi Google Earth Terhadap Kemampuan Berpikir Kronologis dalam Pembelajaran Sejarah Indonesia Kelas X di MA Al-Khairiyah Rancaranji - Mae, Siti Maemunah; Ana, Ana Nurhasanah; Umar, Tubagus Umar Syarif Hadi Wibowo (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This research was conducted to see whether there was an influence from using the Google Earth application on the ability to think chronologically in learning Indonesian history for class X at MA Al-Khairiyah Rancaranji. This study utilized a quasi-experimental approach, and sampling was carried out using the purposive sampling method. This study collected data using pretest and posttest. The results obtained are that the value of the post-test T test is Tcount = 1.66, which is not the same as the Ttable value = 1.67. So, H0 is rejected. H1 is accepted, there is an influence of using the Google Earth application on the ability to think chronologically in learning Indonesian history class X at MA AlKhairiyah Rancaranji. This influence is based on the results of students' answers and observations during the research, namely that students were able to answer questions well after students were given lessons using the Google Earth application.